Cytochrome P450 Bioreactors in the Pharmaceutical Industry: Challenges and Opportunities - Martinez, Carlos A.; Rupashinghe, Sanjeewa G. (Current Topics in Medicinal Chemistry, 2013)
Cytochrome P450 (CYP) bioreactors play a major role in establishing the practical use of this enzyme family in academia and industry. The current demand for enzymatic hydroxylations of unactivated carbons in the parmaceutical industry includes the preparation of drug metabolites and various hydroxylated synthetic precursors as well as the enzyme mediated lead diversification and natural product synthesis, most of which require multigram scale synthesis. To date, the large scale application of CYPs in the synthesis of oxygenated compounds is limited by many challenges. This review describes relevant examples of CYP oxidations and also presents the strategies available to overcome such challenges. At present, P450 catalyzed reactions can only be performed at substrate concentrations ranging from 1-25 mM, unlike other biocatalytic redox reactions like ketone reductases, typically performed at substrate loads greater than 500 mM. The emergence of powerful expression methods and a large number of CYP mutants developed for specific applications holds the promise for future industrial applications. The search for higher volumetric productivities is however a task that needs to be addressed not only through the use of protein engineering as the primary tool but significant emphasis needs to be placed on process development through exploring multiple operating schemes, optimizing reaction media and modifying microbial strains needed for heterologous expression.
Keywords: CYP